Eﬀects of trunk mobility exercise and treadmill training on functional performance of patients with Parkinson’s disease: a single-subject experimental study - Jo, Hye-seong; Oh, Duck-Won (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. This study aimed to investigate the eﬀects of integrating treadmill training with trunk mobility exercise on func-tional performance in patients with Parkinson’s disease (PD).Methods. Fourteen patients with PD volunteered for this study. This single-subject experimental study used an A-B-C design: (A) baseline, (B) intervention-1 (trunk mobility exercise alone), and (C) intervention-2 (trunk mobility exercise and treadmill training). No intervention was performed during the A phase. Trunk mobility exercise focusing on large trunk and limb motions was performed during the B phase. The C phase included treadmill training in addition to trunk mobility exercise. Outcome measures included the 10-m walk test (10MWT), timed up-and-go (TUG) test, uniﬁed Parkinson’s disease rating scale Part III, Berg balance scale, dynamic gait index, and new activities of daily living questionnaire.Results. In the comparison of individual data, most participants showed improved 10 MWT and TUG test scores during the B and C phases when compared with those in the baseline phase, except for one participant for the TUG test score. Moreover, group data comparison revealed signiﬁcantly improved scores for all parameters after the B phase (p < 0.05), and these gains improved synergistically after the C phase (p < 0.05).Conclusions. These ﬁndings suggest that trunk mobility exercises are beneﬁcial for enhancing balance and walking function in patients with PD; furthermore, the beneﬁts are improved synergistically by integrating treadmill training.
Keywords: function; treadmill; exercise; Parkinson’s disease